Sir Ernest Shackleton and the Struggle Against Antarctica - Marcovitz, Hal. (Philadelphia Chelsea House Publishers, 2002)
An English explorer, Shackleton became fascinated at a young age with the frozen region at the southermost point on earth - Antarctica.
5 - 9
Keywords: Shackleton, Ernest Henry, Sir, 1874-1922.; Explorers; Antarctica - Discovery and exploration; Explorers of New Worlds